PEMAKSAAN HUBUNGAN SEKSUAL TERHADAP ISTRI DALAM UU NO 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA (PKDRT) - Putra, Tri Sulatama (LEGALITE, 2017)
Coercion of sexual intercourse is basically inconsistent with good society habits. This act is not in accordance with the human conscience. There have been many rules designed to eradicate bad behavior towards women. Law No. 23 of 2004 on Elimination of Domestic Violence (PKDRT) is one form of government effort to eliminate violence in the family that most of the victims are women. Form of coercion of sexual intercourse with wife according to the Act. No. 23 of 2004 is (1) Unwelcome sexual intercourse of wife due to lack of wife willingness in physical and psychic form. (2) Unwelcome sexual intercourse of a wife, for example, to marry his wife in a drunken husband, to marry a wife while the wife is sleeping wife has never felt inner satisfaction because of the impact of uncomfortable husband's treatment during sex. coercion of a wife's sexual relationship in a state of illness or in a state of wife coming months.